Metabolic Syndrome Predicts Response to Neoadjuvant Chemotherapy in Breast Cancer - Lu, Ying; Wang, Pinxiu; Lan, Ning; Kong, Fei; Abdumijit, Awaguli; Tu, Shiyan; Li, Yanting; Yuan, Wenzhen (Frontiers in Oncology, 2022)
Purpose: This research investigated the predictive role of metabolic syndrome (MetS) in breast cancer neoadjuvant chemotherapy (BCNACT) response. Methods: 150 primary breast cancer (BC) patients who underwent neoadjuvant chemotherapy (NACT) were included retrospectively. MetS, MetS components (waist circumference (WC), fasting blood glucose (FBG), blood pressure, triglycerides (TG), high-density lipoprotein cholesterol (HDL-C)), serum lipid, and other MetS-related laboratory indicators within two weeks before BCNACT were evaluated. Univariate, multivariate, and subgroup analyses were performed to determine the predictors of BCNACT pathologic complete response (pCR), clinical response and pathologic response. The effectiveness of the model was evaluated via ROC curve and calibration curve. External validation was performed through 135 patients. Results: Univariate analysis revealed that MetS before BCNACT predicted poor BCNACT response (pCR, P = 0.003; clinical response, P = 0.033; pathologic response, P＜0.001). Multivariate analysis confirmed that MetS before BCNACT predicted lower pCR rate (P = 0.041). Subgroup analysis showed that this relationship was significant in ER (-) (RR = 0.266; 95% CI, 0.074-0.954), HER2 (-) (RR = 0.833; 95% CI, 0.740-0.939) and TNBC (RR = 0.833; 95% Ci, 0.636-0.995). Multivariate analysis of external validation confirmed that pre-treatment MetS was associated with a lower pCR rate (P = 0.003), and subgroup analysis also confirmed that this relationship had significant statistical differences in ER (-), HER2 (-) and TNBC subgroups. Conclusions: Mets before BCNACT predicted a lower pCR rate. Intervention on MetS status, especially in ER (-), HER2 (-) and TNBC subgroups, is expected to improve the response rate of BCNACT further.